Influence of Sex Preference on Demand for a Child in Bangladesh - Sarkar, Saroje Kumar (International Journal of Statistical Sciences, 2023)
If son preference were to affect the demand for additional children then, within any parity, those with one or more sons would be more likely not to want more children as compared to those who did not have any sons. Conversely, if the desire for a balance sex composition was to affect fertility within a given parity, respondent who had either all sons or all daughters would be more likely to want additional children as compared to those who had children of both sexes. Data from BDHS 2017 clearly indicates a significant evidence of son preference in Bangladesh. The findings indicate that whenever gender preferences would be eliminated, the percentage of respondents who did not want more children would be increased approximately by 10 percent. Finally, we conclude that further reduction of fertility to achieve replacement level is unlikely without considerable reduction in the desire of male children or sex preferences. International Journal of Statistical Sciences, Vol. 23(2), November, 2023, pp 117-127